How Media Coverage of Corporate Social Irresponsibility Increases Financial Risk - Kölbel, Julian F.; Busch, Timo; Jancso, Leonhardt M. (Strategic Management Journal, 2017)
Research summary: This article explores the relationship between corporate social irresponsibility ( CSI ) and financial risk. We posit that media coverage of CSI generates risk by providing conditions that increase the potential for stakeholder sanctions. Through analyzing an international panel of 539 firms during 2008–2013, we find that firms receiving higher CSI coverage face higher financial risk. We show that the reach of the reporting media outlet is a critical condition for this relationship. Once the outlet has a high reach, the severity of CSI coverage is a boundary condition that further reinforces the effect. Our findings complement existing theory about the risk‐mitigating effect of corporate social responsibility by illuminating the risk‐generating effect of CSI coverage. For executives, these insights suggest complementary strategies for corporate risk management . Managerial summary: This article examines the effect of negative news on financial risk. It shows that negative media articles regarding environmental, social, and governance ( ESG ) issues increase a firm's credit risk. It also provides a detailed analysis of the impact of an article's reach and severity, i.e., how many readers are exposed to the article and how harshly it criticizes the firm. The results allow to quantitatively assess the risk that emanates from negative ESG news. For executives, three strategies are derived for limiting a firm's exposure to this risk: balancing corporate social responsibility programs with operational safety programs, reporting suboptimal environmental and social performance transparently and proactively, and avoiding acquisition targets and markets with a legacy of negative news . Copyright © 2017 John Wiley & Sons, Ltd.